MicroCT Can Characterize Clots Retrieved With Mechanical Thrombectomy From Acute Ischemic Stroke Patients–A Preliminary Report - Dumitriu LaGrange, Daniela; Braunersreuther, Vincent; Wanke, Isabel; Berberat, Jatta; Luthman, Siri; Fitzgerald, Seán; Doyle, Karen M.; Brina, Olivier; Reymond, Philippe; Platon, Alexandra; Muster, Michel; Machi, Paolo; et al. (Frontiers in Neurology, 2022)
Background: Characterization of the clot occluding the arteries in acute ischemic stroke received ample attention, in terms of elucidating the relationship between the clot composition, its etiology and its amenability for pharmacological treatment and mechanical thrombectomy approaches. Traditional analytical techniques such as conventional 2D histopathology or electron microscopy sample only small parts of the clot. Visualization and analysis in 3D are necessary to depict and comprehend the overall organization of the clot. The aim of this study is to investigate the potential of microCT for characterizing the clot composition, structure and organization. Methods: In a pilot study, we analyzed with microCT clots retrieved from 14 patients with acute ischemic stroke. The following parameters were analyzed: overall clot density, clot segmentation with various density thresholds, clot volume. Results: Our findings show that human clots are heterogeneous in terms of CT intra-clot density distribution. After fixation in formalin, the clots display a shift towards negative values. On average, we found the mean HU values of red clots retrieved from patients to be -153 HU, with SD=23.8 HU, for the intermediate clots retrieved from patients - 193 HU, SD= 23.7 HU, and for the white clots retrieved from patients -229 HU, SD=64.8 HU. Conclusion: Our study shows that volumetric and density analysis of the clot opens new perspectives for clot characterization and for a better understanding of thrombus structure and composition.